2020
DOI: 10.4081/ejtm.2020.8957
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electromyographic activity during Nordic hamstring exercise and exercises in lengthened position

Abstract: Hamstring strain injuries remain among the most problematic and most frequent sport injuries. Two of the most effective methods for prevention and rehabilitation of the hamstring strain injuries are: classic eccentric training using the Nordic hamstring exercise (NHE) and eccentric training in a lengthened position using the glider exercise. Both exercises have disadvantages that could be fixed by adding hip flexion during the NHE. Thus, the purpose of the study was to compare peak hamstring activity (measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Only three studies reported data of NHE performances with high eccentric control beyond knee flexion angles of <45° [ 6 , 40 , 84 ]. Two recent studies which investigated NHE with 90° hip flexion only included participants who were able to perform more than 50% of the NHE knee ROM in a controlled manner [ 18 , 77 ]. Based on these small numbers, it can be assumed that most of the included NHE studies analyzed the performance and effects of the NHE, which involved a premature ending of the controlled eccentric action (<40° from the vertical) and a significant decrease in muscle activation [ 41 , 43 , 46 , 71 , 82 , 97 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only three studies reported data of NHE performances with high eccentric control beyond knee flexion angles of <45° [ 6 , 40 , 84 ]. Two recent studies which investigated NHE with 90° hip flexion only included participants who were able to perform more than 50% of the NHE knee ROM in a controlled manner [ 18 , 77 ]. Based on these small numbers, it can be assumed that most of the included NHE studies analyzed the performance and effects of the NHE, which involved a premature ending of the controlled eccentric action (<40° from the vertical) and a significant decrease in muscle activation [ 41 , 43 , 46 , 71 , 82 , 97 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should include a gradual approach to proper execution technique. Facilitations such as assistance (e.g., by elastic bands) [ 6 , 48 , 53 , 76 ] or shank inclination [ 18 , 44 , 75 , 77 ] might be implemented to convey the feeling for the constantly high muscle activation and to facilitate the control of the gravity-induced and progressively increasing overload during the last part of the ROM [ 55 , 101 , 105 ]. Thorough familiarization will improve the quality, reliability, and consistency of NHE performance [ 66 , 68 , 70 , 106 , 107 , 108 ] and consequently, the detection of players at elevated injury risk [ 109 , 110 , 111 , 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In amateur football, it has been reported that injuries occur on average 20 to 37 times in every 1000 matches and 2 to 4 times in every 1000 training sessions [5]. Among the injuries that occur, hamstring muscle injuries are seen as one of the most common lower extremity musculoskeletal injuries [6][7][8][9]. While an average of 5-6 hamstring injuries occurs in each team during a season, it accounts for 12% to 16% of all injuries in adult men's football [10].…”
mentioning
confidence: 99%